Otoritas Pemerintah Daerah Dalam Konteks Hukum Internasional Tinjauan Hukum Otonomi Daerah - Nugraha, Safri (Indonesian Journal of International Law, 2006)
The Development of Democracy principles in Indonesia has promoted the policy of regional autonomy based on regional interest. The policy of regional autonomy needs to be supported by legal infrastructure in order to provide the certainty of the legal principle and justice value. In relation to the recent global development, the international relationship particularly in term of economic and business field is significantly developed to the sophisticated situation. Therefore, it is highly important to do in depth research on the functions and the relations between the central and the regional authorities concerning on their competency to establish an international relationship. Government of Indonesia itself has developed the administration system consist of Central Administration and Regional Administration which each has different competency as regulated in Law No. 32 Year 2004 on Regional Administration ("Law"). In conducting its competency, the central government is dealing with national scope matters, and the regional administration is handling the matters in the region or local area.